QUANTITATIVE ELEMENTAL ANALYSIS OF LEADING PETROTYPES OF PRECAMBRIANS UKRAINIAN SHIELD GRANITOIDS WITH VIEW OF CLEARING UP OF THEIR METALOGENIC PECULIARITIES - TOLSTOI, M.; KOSTENKO, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2004)
The results are demonstrated of quantitative distribution analysis of chemical elements in leading petrotypes of granitoids complexes of Ukrainian shield with view determination among them most perspective for searches of the ores of less-common metals.